2006
DOI: 10.1186/bcr1533
|View full text |Cite|
|
Sign up to set email alerts
|

The mTOR inhibitor rapamycin down-regulates the expression of the ubiquitin ligase subunit Skp2 in breast cancer cells

Abstract: Introduction Loss of the cyclin-dependent kinase inhibitor p27 is associated with poor prognosis in breast cancer. The decrease in p27 levels is mainly the result of enhanced proteasome-dependent degradation mediated by its specific ubiquitin ligase subunit S phase kinase protein 2 (Skp2). The mammalian target of rapamycin (mTOR) is a downstream mediator in the phosphoinositol 3' kinase (PI3K)/Akt pathway that down-regulates p27 levels in breast cancer. Rapamycin was found to stabilize p27 levels in breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 30 publications
3
51
0
2
Order By: Relevance
“…In addition, RAD001 might control the protein levels of p27Kip1 by down-regulating its specific ubiquitin ligase subunit, Skp2 (24). We found both cyclin D1 and cyclin D3 proteins up-regulated in mutant thyroids compared with wild-type controls, whereas p27Kip1 levels were not altered by Pten loss (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…In addition, RAD001 might control the protein levels of p27Kip1 by down-regulating its specific ubiquitin ligase subunit, Skp2 (24). We found both cyclin D1 and cyclin D3 proteins up-regulated in mutant thyroids compared with wild-type controls, whereas p27Kip1 levels were not altered by Pten loss (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Inhibition of mTORC1 has been shown to stabilise p27 mRNA and to promote cap-independent translation of p27 mRNA, hence both mRNA and protein levels may be upregulated independent of gene activation [31]. A recent study in human breast-cancer cell lines has shown that inhibition of mTORC1 with rapamycin also leads to reduced p27 protein degradation via decreased expression of the ubiquitin ligase subunit Skp2 [41]. Hence the early increase in p27 protein levels may also be due to a decrease in p27 degradation.…”
Section: Resultsmentioning
confidence: 99%
“…43,44 Recently, it was shown that mouse embryonic fibroblasts deficient in the transcription factor Oct1 were insensitive to mTOR inhibition by rapamycin. 45 Oct1 was found to control transcription of p27 Kip1 in wild-type cells downstream of the mTOR pathway such that Oct1 negative cells failed to upregulate p27 Kip1 in response to rapamycin.…”
Section: A Comparative Analysis Of Rapamycin Effect On Rat Liver Cellmentioning
confidence: 99%